2012
DOI: 10.1182/blood-2011-10-387266
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of murine normal and stress-induced erythropoiesis by Desert Hedgehog

Abstract: The function of Hedgehog signaling in hematopoiesis is controversial, with different experimental systems giving opposing results. Here we examined the role of Desert Hedgehog (Dhh) in the regulation of murine erythropoiesis. Dhh is one of 3 mammalian Hedgehog family proteins. Dhh is essential for testis development and Schwann cell function. We show, by analysis of Dhh-deficient mice, that Dhh negatively regulates multiple stages of erythrocyte differentiation. In Dhh-deficient bone marrow, the common myeloid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 45 publications
2
35
0
Order By: Relevance
“…Interestingly, Dhh is expressed at significantly lower levels and observed later during recovery, which is consistent with its role as a negative regulator. 32 Furthermore, the expression of Epo in the kidney is not induced until day 6, which correlates with the initial increase in CD34 …”
Section: Cd34 and Cd133 Expression Marks A Developmental Progression mentioning
confidence: 91%
“…Interestingly, Dhh is expressed at significantly lower levels and observed later during recovery, which is consistent with its role as a negative regulator. 32 Furthermore, the expression of Epo in the kidney is not induced until day 6, which correlates with the initial increase in CD34 …”
Section: Cd34 and Cd133 Expression Marks A Developmental Progression mentioning
confidence: 91%
“…Genotyping of Kif7 mutant mice by PCR was performed as described [37] with primers neo (5′-GCAGCGCATCGCCTTCTATCG-3′), exon 2 (5′-GGCGGGACCGACACTTTGGG-3′), and intron 2 (5′-CACCTGACATGGAGTGCTGACC-3′), generating a 302 bp product in WT and 197 bp product in knockout allele.…”
Section: Methodsmentioning
confidence: 99%
“…While Desert hedgehog (Dhh) has been reported to be a negative, i.e. inhibiting, regulator of the proliferation and differentiation of steady-state and stress progenitors, it has been demonstrated that some hedgehog signaling is required for ensuring sensitivity of stress progenitors to the BMP4-induced stress response (Lau et al, 2012, Perry et al, 2009). …”
Section: Pathogenesismentioning
confidence: 99%